Severe form of streptococcal necrotizing fasciitis of the upper limb – diagnostic and therapeutic challenge: A case report - Mikić, Dragan; Takić-Radovanović, Tatjana; Luković, Milan; Košutić, Milomir; Starčević, Srdjan; Bjelanović, Zoran; Djordjević, Dragan; Nožić, Darko (Vojnosanitetski pregled, 2015)
Introduction. Since delay in recognition and effective treatment of necrotizing fasciitis (NF) caused by invasive group A streptococcus increases the mortality and disability, the early diagnosis and management of this disease are essential for a better outcome. We presented a patient with a severe form of streptococcal NF of the left upper limb in whom amputation was performed as a life saving procedure. Case report. A 65-year-old man, previously healthy, suffered an injury to his left hand by sting on a fish bone. Two days after that the patient got fever, redness, swelling and pain in his left hand. Clinical examination of the patient after admission indicated NF that spread quickly to the entire left upper limb, left armpit, and the left side of the chest and abdomen. Despite the use of aggressive antibiotic and surgical therapy severe destruction of the skin and subcutaneous tissues developed with the development of gangrene of the left upper limb. In this situation, the team of specialists decided that the patient must be operated on submited to amputation of the left arm, at the shoulder. After amputation and aggressive debridement of soft tissue on the left side of the trunk, the patient completely recovered. β-hemolytic streptococcus group A was isolated from the skin and tissue obtained during the surgery. Conclusion. In the most severe forms of streptococcal NF of the extremities, adequate multidisciplinary treatment, including limb amputation, can save the life of a patient.